Ubiquitination regulates allergic asthma by affecting immune cells and immune responses - Zheng Jin; Zhenhua Zhu; Xiaopeng Jing; Ji Zeng; Dongmei Yan (Biochemistry and Biophysics Reports)
Allergic asthma, known for its airway hyperresponsiveness and remodeling, is a prevalent chronic respiratory disease. Recent investigations have emphasized the crucial role of ubiquitination, a post-translational modification, in the pathogenesis of allergic asthma. Ubiquitination involves the addition of ubiquitin molecules to substrates, caused their degradation or alteration in activity. Ubiquitination affects various aspects of immune cell function, such as activation of Th2 cells, B cells, and antigen-presenting cells, which are vital to allergic asthma.In this review, we explore the role of ubiquitination in modulating immune responses during allergic asthma. We discuss the interplay between ubiquitin ligases, their substrates, and the impact on immune cell function, including Th2 differentiation and Th2 cytokines production. Our study also considers the potential therapeutic outcomes of targeting ubiquitination in asthma management. By understanding the complex interplay between ubiquitination, immune cells and immune responses, we can identify new molecules for treating allergic asthma, potentially leading to more effective therapies that modulate immune responses and ameliorate disease symptoms.